Mating Delay Reduces Reproductive Performance but not Longevity in a Monandrous Moth. Issue 2 (2nd March 2020) - Zheng, Xia-Lin; Liu, Junyan; Lu, Wen; He, Xiong Zhao; Wang, Qiao
Abstract: Age at mating is one of the most important factors that affect mating success and reproductive fitness in insects. The present study investigated how the age of the two sexes at mating determined mating success, reproductive fitness and longevity in Phauda flammans (Walker) (Lepidoptera: Phaudidae), a serious pest of Ficus spp. trees in South and Southeast Asia. The study may provide basic knowledge for the development of mating disruption programs using sex pheromones to control this pest. The species is monandrous and its adults live for only 4–5 d. We show that delayed mating significantly lowered mating success in both sexes, with males being more severely affected than females. Mating delay also reduced reproductive outputs of both sexes but females were more negatively affected than males. We did not find any effect of delayed mating on longevity of either sex. Our findings suggest that mating disruption with sex pheromones can be an effective method to delay mating in P . flammans, reducing reproductive success and thus limit population growth.